2013
DOI: 10.1093/cvr/cvt224
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite activates protein kinase A in normoxia to mediate mitochondrial fusion and tolerance to ischaemia/reperfusion

Abstract: These data are the first to demonstrate nitrite-dependent normoxic modulation of both mitochondrial morphology and function and reveal a novel signalling pathway responsible for nitrite-mediated cardioprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 65 publications
7
75
0
Order By: Relevance
“…This unexpected result may be due to the pleiotropic nonfusion effects of these mitochondrial fusion proteins that include apoptosis induction, mediation of mitophagy, and tethering the sarcoplasmic reticulum to the mitochondria (de Brito and Scorrano, 2008a,b;Wang et al, 2012). A recent study has shown that pharmacologic preconditioning using nitrite protected a cardiac cell line by inhibiting ischemia-induced mitochondrial fission through the activation of protein kinase A (Pride et al, 2014). Whether ischemic preconditioning and postconditioning exert their cardioprotective effect by modulating mitochondrial morphology is not known.…”
Section: Confounders Of Cardioprotection 1145mentioning
confidence: 99%
“…This unexpected result may be due to the pleiotropic nonfusion effects of these mitochondrial fusion proteins that include apoptosis induction, mediation of mitophagy, and tethering the sarcoplasmic reticulum to the mitochondria (de Brito and Scorrano, 2008a,b;Wang et al, 2012). A recent study has shown that pharmacologic preconditioning using nitrite protected a cardiac cell line by inhibiting ischemia-induced mitochondrial fission through the activation of protein kinase A (Pride et al, 2014). Whether ischemic preconditioning and postconditioning exert their cardioprotective effect by modulating mitochondrial morphology is not known.…”
Section: Confounders Of Cardioprotection 1145mentioning
confidence: 99%
“…It is also recognized that several modalities of pharmacological preconditioning and ischemic preconditioning involve the modulation of mitochondrial number and function (23,97,139,149). Consistent with this, accumulating data demonstrates that nitrite regulates mitochondrial number, function and morphology in both ischemic and non-hypoxic conditions (37,50,86,103,109,120,121,145,191). This review will provide an overview of the preclinical studies demonstrating nitrite-mediated protection, focus on the distinct mechanisms by which nitrite regulates hypoxic and non-hypoxic mitochondrial function and discuss the contribution of these mechanisms to nitrite-mediated preconditioning and cytoprotection after I/R.…”
Section: Introductionmentioning
confidence: 84%
“…We have shown in vivo that administration of one dose of nitrite by oral gavage 24 hours prior to the ischemic episode confers protection in a murine model of myocardial infarction or hepatic I/R (195). Further, hearts isolated from rats given one dose of intraperitoneal nitrite show a significant decrease in infarct size and protection of left ventricular developed pressure after ex vivo global ischemia/reperfusion (103). It is important to note that the half-life of nitrite in blood and in the non-hypoxic heart and liver is less than one hour (43,47) suggesting that the nitrite administered systemically to non-hypoxic animals in these studies is fully metabolized well before the tissue is exposed to ischemia.…”
Section: Nitrite As a Pharmacological Delayed Preconditioning Agentmentioning
confidence: 96%
See 2 more Smart Citations